2022
DOI: 10.1002/ps.7248
|View full text |Cite
|
Sign up to set email alerts
|

Effective control of Leptosphaeria maculans increases importance of L. biglobosa as a cause of phoma stem canker epidemics on oilseed rape

Abstract: BACKGROUND: Phoma stem canker is a damaging disease of oilseed rape caused by two related fungal species, Leptosphaeria maculans and L. biglobosa. However, previous work has mainly focused on L. maculans and there has been little work on L. biglobosa. This work provides evidence of the importance of L. biglobosa to stem canker epidemics in the UK. RESULTS: Quantification of L. maculans and L. biglobosa DNA using species-specific quantitative PCR showed that L. biglobosa caused both upper stem lesions and stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…This hypothesis is indirectly supported by previous results on timing/ abundance of L. maculans and L. biglobosa ascospore release and the severity of phoma stem canker in field experiments. 20,47 For example, for the field experiments with nine cultivars, the mean severity of stem canker in the summer of 2012 (i.e., 2.28) was less than that in the summer of 2011 (i.e., 4.03). This may have been due to ascospores of L. biglobosa being released earlier with a larger amount than ascospores of L. maculans in the autumn 2011 20 so that L. biglobosa could have inhibited the growth of L. maculans leading to less severe canker in the summer of 2012.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This hypothesis is indirectly supported by previous results on timing/ abundance of L. maculans and L. biglobosa ascospore release and the severity of phoma stem canker in field experiments. 20,47 For example, for the field experiments with nine cultivars, the mean severity of stem canker in the summer of 2012 (i.e., 2.28) was less than that in the summer of 2011 (i.e., 4.03). This may have been due to ascospores of L. biglobosa being released earlier with a larger amount than ascospores of L. maculans in the autumn 2011 20 so that L. biglobosa could have inhibited the growth of L. maculans leading to less severe canker in the summer of 2012.…”
Section: Discussionmentioning
confidence: 97%
“…11,16 However, recent studies have found that in the UK, ascospores of L. maculans and L. biglobosa can be released at similar times, and that L. biglobosa can cause stem basal cankers, especially on cultivars with effective resistance genes against L. maculans. 20 When interspecific competition occurs, it can manifest in three different ways. 1 Resource-mediated (exploitation) competition arises when a resource becomes limited, whereby the species that can use the resource most efficiently outcompetes the others and survives, sometimes even leading to competitive exclusion of other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Collection and quantification of airborne fungal propagules are now routine and feature prominently in arriving at both prophylactic and therapeutic decisions for the management and control of plant diseases caused by aerially dispersed fungal inoculum. 13,37,38 Since the initial conception of Hirst-type air samplers by Gregory 39 and Hirst 40 (reviewed by West and Kimber 41 ), advances in the coupling of the methods of aerobiology and techniques of wind-dispersed fungal propagule collection, detection and quantification have enabled earlier, easier and more effective decisions in disease management. [42][43][44][45] Taken together, the integration of spore trapping with quantitative diagnostic assays such as qPCR can facilitate and enhance a faster and more accurate assessment than by abundance estimation made by spore counting on light microscope slides, particularly if these spores are difficult to identify visually at the species and infra-species levels, which is very often the case with phytopathogens of important crop plants.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It has been also demonstrated that effective control of one species increases the importance of the other. 27 The bad news is that fungal infection may increase palatability of oilseed rape to insects. 28 The re-disposition of Phoma-like anamorphs in Pleosporales done 10 years ago led to further change in fungus taxonomy; L. maculans has been re-named Plenodomus lingam, whereas L. biglobosa has been termed P. biglobosus.…”
Section: Integrated Pest Control In Oilseed Crops-new Advances From T...mentioning
confidence: 99%